Bacteriophage-driven microbial phenotypic heterogeneity: ecological and biogeochemical importance - Xiaolong Liang; Shuo Yang; Mark Radosevich; Yongfeng Wang; Ning Duan; Yongfeng Jia (npj Biofilms and Microbiomes)
Abstract Bacteriophages (phages) reprogram host metabolism and generate phenotypic heterogeneity, yet the mechanisms and ecological implications remain poorly understood representing a major knowledge gap in microbial ecology. This review explores how phage infection alters microbial physiology, contributes to single-cell variation, and influences population dynamics. We highlight the potential consequences of phage-driven heterogeneity for microbial community structure and biogeochemical cycling, underscoring the importance of integrating phage-host interactions into ecological and ecosystem models.